Clinical approach in users with cognitive behavioral therapy - Chirio Aldazabal, Diego Bernardo (2023)
The professional in psychology that develops in applied areas, must resort to the currents of knowledge that are within what we call psychology, all this to enhance the scope of their objectives, which in clinical practice, are called as Therapeutics The purpose of the present work is to develop a review of the clinical approach in users with behavioral-cognitive therapy. It is considered the absence of a body of unified knowledge and is encouraged not to be content with only one contribution, but complement it with others, as if it were to complete a puzzle (metaphorically). It emphasizes the need for knowledge about learning theories, proposals for the formulation of the case and review of studies on empirical support of different therapeutic strategies. It is concluded that both behavioral and cognitive strategies allow us to have not only a series of procedures, but reference frameworks to be able to interpret the specific-circusing events that the professional in psychology is daily.